Paternalistic intervention : the moral bounds on benevolence - Vandeveer, Donald (Princeton : Princeton University Press, 1986)
Donald VanDeVeer probes the moral complexities of the question: under what conditions is it permissible to intervene invasively in the lives of competent persons--for example, by deception, force, or coercive threat--for their own good? In a work with broad significance for law, public policy, professional-client relations, and private interactions, he presents a theory of an autonomy-respecting"" paternalism. Originally published in 1986. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the.
1. The Nature and Scope of Paternalism -- 2. Appeals to Consent -- 3. Appeals to Doing Good -- 4. The Doctrine of Informed Consent -- 5. Death, Sex, Odysseus and the Sirens -- 6. Paternalistic Limits on Risk Taking -- 7. Our Dealings with Incompetents -- 8. Overview, Reservations, and Implications.
Elektronická reprodukce.
Keywords: paternalismus -- etické a morální aspekty; paternalism -- ethical and moral aspects; e-knihy online; e-books online